A cognitive perspective on animal-based similitative derivatives in Polish - Kielak, Olga (Papers in Linguistics, 2023)
The study analyses nationwide, dialectal and sociolectal word-formations (nominal, adjectival and verbal structural derivatives) created from the names of selected domestic animals. Following Ronald Langacker’s proposal, the author tries to answer the question how new words are formed. In addition, the analysis of the collected material shows what derivatives reveal about the human conceptualisation of the world and how Ronald Langacker’s Cognitive Grammar and Jerzy Bartmiński’s Lublin-based Ethnolinguistics are close to each other.